A Comment on: “On the Informativeness of Descriptive Statistics for Structural Estimates” by Isaiah Andrews, Matthew Gentzkow, and Jesse M. Shapiro - Bonhomme, Stéphane (Econometrica, 2020)
LET ME FIRST BRIEFLY RECALL the bias expressions in the paper.For simplicity, throughout I will fix a value η of the base model parameter.Let f η ζ be the density of the data D under the reader's model.Let f η denote the density of D under the base model.Given a quantity of interest c(η), the unrestricted bias of c is